Work Culture, Workload, and Job Satisfaction Intervening a Public Hospital Nurses’ Performance - Adhikara, Arrozi; Rahmawati, Wawah; Musaida, Musaida (Interdisciplinary Social Studies, 2022)
Based on preliminary data taken by researchers, with 15 nurses at BA Tangerang Public Hospital, from the questionnaires distributed, in the aspect of job satisfaction nurses obtained results that all nurses filled in at least 1 indicator of dissatisfaction, namely 80% dissatisfied in terms of salary, 60% dissatisfied in terms of job promotion and 6% dissatisfied in terms of supervision.  In terms of workload, 4 nurses did not report workload issues, and 11 nurses, or 73 percent, reported workload issues. Specifically, 81 percent of respondents reported that their working hours increased during each shift, 27 percent reported that the shifts were too long, 9 percent reported receiving duplicate tasks, 9 percent worked in confined spaces, and 9 percent worked in uncooled rooms. In the aspect of Work Culture, it was found that 87% had a good work culture and 13% had work culture problems. In the aspect of nurse performance, it was found that 20% of nurses had performance problems. To analyze the influence of work culture, workload, and job satisfaction on the performance of nurses at BA Tangerang Public Hospital. The research method uses an exploratory causality research design conducted on 130 respondents. The results of the study show that Work Culture, Workload, and Job Satisfaction have a significant influence on the performance of nurses at BA Tangerang Public Hospital.